Budgetary participation and performance: some Malaysian evidence - Yahya, Mohd Nor Yahya; Nik Ahmad, Nik Nazli; Fatima, Abdul Hamid (Emerald, 2008)
Purpose – The purpose of this paper is to explore the budgetary participation and performance (BPP) relationship in a public sector organization in a developing country, Malaysia. It also attempts to examine whether organizational commitment and perception of innovation mediate the BPP relationship.